Influence of the parameters of organic matter stimulation with the electromagnetic field on the characteristics and structure of the generated thermal energy. Issue 1 (1st December 2022) - Popardowski, E; Kiełbasa, P; Rad, M; Dróżdż, T
Abstract: The article presents the change in temperature to time ratio of the solenoid winding depending on the working fluid flow. This measurement is extremely important from the point of view of the stimulation of biological material using the electromagnetic field, due to the possibility of denaturing the protein of the organic substance, which transfer into false experimental results. The differences in temperature to time ratio between the coil winding and the working fluid were presented and the results were supplemented with pictures from a thermal imaging camera. An attempt was also made to determine the theoretical reserve of the thermal energy flux. The obtained results will be used to create a system that will fully automatically control the set temperature of the cooling liquid, with the possibility of its cyclical changes.